2004
DOI: 10.1002/app.13573
|View full text |Cite
|
Sign up to set email alerts
|

PMMA/silica nanocomposite studies: Synthesis and properties

Abstract: Polymethylmethacrylate (PMMA)/silica nanocomposites are prepared by solution polymerization in this project and the resulting materials are subjected to characterization to evaluate thermal, mechanical, and fire properties. IR results show that both (3-acryloxypropyl)methydimethoxysilane (APMDMOS) and (3-acryloxypropyl)trimethoxysilane (APTMOS) can serve as reagents for the surface modification of silica, while APTMOS performed better than APMDMOS for the modification of the silica surface. Mechanical properti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
98
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(102 citation statements)
references
References 16 publications
3
98
1
Order By: Relevance
“…It was shown that the addition of silica into PMMA improves thermal stability of the composites. This improved thermal stability was explained by the hindered mobility of the polymer chains due to the presence of filler, 15 the ability of silica nanoparticles to trap radicals during PMMA degradation and to act as a gas barrier preventing the degradation products from diffusing out of the composite, 14 or through a hydrogen-bonding interaction between carbonyl groups in PMMA and hydroxyl groups of the silica surface, 16 where hydrogen bonds interrupt the depolymerization of the polymer Japi} et al: Effect of ZnO on the Thermal Degradation Behavior ... chains. Similarly to silica, the addition of Fe 2 O 3 and TiO 2 nanoparticles into PMMA also influence the composite thermal stability.…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that the addition of silica into PMMA improves thermal stability of the composites. This improved thermal stability was explained by the hindered mobility of the polymer chains due to the presence of filler, 15 the ability of silica nanoparticles to trap radicals during PMMA degradation and to act as a gas barrier preventing the degradation products from diffusing out of the composite, 14 or through a hydrogen-bonding interaction between carbonyl groups in PMMA and hydroxyl groups of the silica surface, 16 where hydrogen bonds interrupt the depolymerization of the polymer Japi} et al: Effect of ZnO on the Thermal Degradation Behavior ... chains. Similarly to silica, the addition of Fe 2 O 3 and TiO 2 nanoparticles into PMMA also influence the composite thermal stability.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, a substantial improvement of the thermo-mechanical properties of polymer matrices has been reached by the introduction of high aspect ratio fillers, such as carbon nanotubes [2][3][4] and layered silicates [5][6][7][8][9][10]. Compared to the extended literature concerning these kinds of nanofillers, relatively few attention has been devoted to nanocomposites filled with metal oxide nanoparticles, such as fumed titania [11,12] and fumed silica [13][14][15]. For instance, Chaichana et al [16] developed a novel route to synthesize linear low density polyethylene (LLDPE)/nanosilica systems via in situ polymerization with a zirconocene/methyl alumoxane (MAO) catalyst, in order to study the effect of particle size on the catalytic properties of the resulting materials.…”
Section: Introductionmentioning
confidence: 99%
“…Yang et al [115] synthesized PMMA/silica nanocomposite membranes via solution polymerization. Two different types of coupling agents, namely APMDMOS and APTMOS, were used.…”
Section: With Silica/nanoparticlesmentioning
confidence: 99%